Chemical Castration Sanctions for Perpetrators of Child Sexual Violence in the Frame of Islamic Criminal Law - Rachmadani Rachmadani; Sarwo Zulfahmi Muhammad Daming (Al-'Adl, 2021)
This article discusses the review of Islamic criminal law regarding sanctions castration chemistry for the perpetrators of sexual violence against children. It is motivated by the rampant cases of sexual crimes against children have increased every year. As a response to the things that President Joko Widodo has issued Government Regulation No.. 70 Year 2020 about procedures for the Implementation of the Action Castration Chemistry, the Installation of the Detector Electronics, Rehabilitation and the Announcement of the Identity of the Perpetrators of Sexual Violence against Children. This rule gave authority to the state to be able to impose sanctions castration chemistry for the perpetrators of sexual violence against children. As for the problem studied in this research is how the forms of sexual violence in children? and how the determination of sanctions castration chemistry for the perpetrators of sexual violence against children is viewed from the perspective of the criminal law of Islam? This study uses the approach of normative juridical to discover the basics of the law of the criminal law of Islam-related sanctions gelding chemical. While methods of data collection using the method of literature, after the data collected then analyzed and interpreted by means of deductive. The results showed sanctions gelding chemical was done as an attempt of recovery of sexual disorders, so it can be said this punishment is not as torture against the perpetrators. As for the sanctions gelding chemical in the perspective of Islamic criminal law can be categorized punishment ta'zir which is a sentence that has a minimum and a maximum that is determined by a judge. The judge reserves the right to impose a penalty gelding chemical if the defendant is convicted of a violation based on the applicable law, because of the type of punishment is not in the nash.